The Role of SMEs in Enhancing the Economy: A Case Study of the Alamanda Women's Craft Group - N. Nurbaeti; Yunus Sading; Armin Muis; Anwar Nasruddin; N. Nurnaningsih (Manunggal Halim Jaya, 2024)
The role of Micro, Small, and Medium Enterprises (SMEs) in economic development is particularly significant for the Alamanda Women's Craft Group in Watutau Village, impacting both human resources and income, which contribute to economic improvement. This descriptive qualitative and quantitative study emphasizes process and meaning through analysis. Data collection is the initial step in this study, involving interviews, documentation, and observation, which lead to the conclusion. The object of this research is the Alamanda Women's Craft Group SMEs in Watutau Village, Lore Peore District. The results of this study indicate that SMEs play a crucial role in enhancing the economy, particularly for members of the Alamanda Women's Craft Group. This conclusion is supported by evidence of job creation and improved community welfare, aligned with the economic growth observed.